Recent advances in gene-editing approaches for tackling antibiotic resistance threats: a review - Al-Fadhli, Amani H.; Jamal, Wafaa Yousef (Frontiers in Cellular and Infection Microbiology, 2024)
Antibiotic resistance, a known global health challenge, involves the flow of bacteria and their genes among animals, humans, and their surrounding environment. It occurs when bacteria evolve and become less responsive to the drugs designated to kill them, making infections harder to treat. Despite several obstacles preventing the spread of genes and bacteria, pathogens regularly acquire novel resistance factors from other species, which reduces their ability to prevent and treat such bacterial infections. This issue requires coordinated efforts in healthcare, research, and public awareness to address its impact on human health worldwide. This review outlines how recent advances in gene editing technology, especially CRISPR/Cas9, unveil a breakthrough in combating antibiotic resistance. Our focus will remain on the relationship between CRISPR/cas9 and its impact on antibiotic resistance and its related infections. Moreover, the prospects of this new advanced research and the challenges of adopting these technologies against infections will be outlined by exploring its different derivatives and discussing their advantages and limitations over others, thereby providing a corresponding reference for the control and prevention of the spread of antibiotic resistance.